Does the empty follicle syndrome occur in cases of low number of maturing follicles in assisted reproduction?. (3rd April 2019) - Yakovi, Shiran; Izhaki, Ido; Ben-Ami, Moshe; Younis, Johnny S.
Abstract: The pathophysiology of the genuine empty follicle syndrome (EFS) is still debated. Ovarian aging has been contested as a cause of this condition. Our aim was to investigate the occurrence of the genuine EFS in cases of a low number of mature follicles in a prospective manner. Ninety-five infertile women were recruited and evaluated following conventional controlled ovarian stimulation (COS) with ≤ six follicles of ≥14 mm diameter on the day of hCG administration. Enrolled women were 37.5 ± 5.2 years of age with basal FSH level of 9.1 ± 3.7 mIU/L, antral follicle count (AFC) of 6.9 ± 4.6, and number of ≥14 mm follicles (on the day of hCG) of 3.4 ± 1.5. Among the 95 women, four were complicated by the genuine EFS (4.2%) with features of the depleted ovarian reserve. Comparison between these four cases and the 91 controls revealed significant differences between age, AFC, number of ≥14 mm follicles, and serum E2 level corresponding to 41.8 ± 1.7 versus 37.4 ± 5.2 years, 1.7 ± 0.6 versus 7.1 ± 4.5, 2.0 ± 0.8 versus 3.4 ± 1.5 follicles, and 356 ± 200 versus 975 ± 557 pg/mL, respectively. Post hoc analysis revealed that 56 among the 95 women fulfilled the Bologna criteria for poor ovarian response and all four cases matched the definition of the genuine EFS raising its incidence to 7.1% in this group. A logistic regression analysis showed that AFC was a significant factor in the development of the genuine EFS. We conclude that the genuine EFS complicates infertile women characterized by a low number of mature follicles. Our findings suggest that the mechanism behind this occurrence is associated with a more exhausted ovarian reserve.